Sibyls, scriptures, and scrolls : John Collins at seventy - Collins, John J. 1946-; Baden, Joel S., 1977-; Najman, Hindy.; Tigchelaar, Eibert J. C. (Supplements to the Journal for the Study of Judaism, 2016)
This volume, a tribute to John J. Collins by his friends, colleagues, and students, includes essays on the wide range of interests that have occupied John Collins's distinguished career. Topics range from the ancient Near East and the Hebrew Bible to the Dead Sea Scrolls and Second Temple Judaism and beyond into early Christianity and rabbinic Judaism. The contributions deal with issues of text and interpretation, history and historiography, philology and archaeology, and more. The breadth of the volume is matched only by the breadth of John Collins's own work.